The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1089/jmf.2013.0015
|View full text |Cite
|
Sign up to set email alerts
|

Lentinula edodes (Shiitake) Modulates Chemically Induced Mutagenesis by Enhancing Pitting

Abstract: This study was undertaken to understand how Lentinula edodes modulates in vivo mutagenesis induced by alkylating agents in bone marrow and peripheral blood as described in our previous article. Male Swiss mice were pretreated for 15 consecutive days with aqueous extracts prepared from L. edodes, after which, the number of circulating blood cells, normal erythroid bone marrow cell cycling, and phagocytosis of micronucleated reticulocyte (MNRET) and activation of spleen macrophages were assessed. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This observation may be explained by comparing results from micronuclei and splenic phagocytosis, which showed increased phagocytic activity in spleens from C. adamantium-treated mice. It is known that the spleen removes defective cells from the bloodstream, including micronucleated cells (de Lima et al, 2013). Therefore, this finding supports the hypothesis that the extract is capable of inducing cellular DNA damage.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This observation may be explained by comparing results from micronuclei and splenic phagocytosis, which showed increased phagocytic activity in spleens from C. adamantium-treated mice. It is known that the spleen removes defective cells from the bloodstream, including micronucleated cells (de Lima et al, 2013). Therefore, this finding supports the hypothesis that the extract is capable of inducing cellular DNA damage.…”
Section: Discussionsupporting
confidence: 84%
“…For each animal, 200 cells were analyzed using a fluorescence microscope at 400X magnification, a 420-490-nm excitation wavelength, and a 520-nm barrier filter. The analysis was performed as previously described by Hayashi et al (1990) and adapted by de Lima et al (2013).…”
Section: Spleen Phagocytosis Evaluationmentioning
confidence: 99%
“…In addition, animals pre-treated with extract prepared with powder stored at -20 ºC exhibited increased basal DNA damage when compared with the untreated control animals, demonstrating that storage can alter the biological properties of bio-compounds and, in such a case, result in genotoxic effects (LIMA et al, 2010). The same research group demonstrated that L. edodes extracts facilitate the removal of circulating erythrocytes with intraerythrocytic inclusions, such as micronuclei and protozoa, from phagocytosis by splenic macrophages, in a process known as pitting (LIMA et al, 2013).…”
Section: The Biological Effect Of Natural Products Obtained From Micr...mentioning
confidence: 97%
“…Polysaccharides obtained from edible mushrooms, such as Lentinus edodes (shiitake) and Agaricus brasiliensis (sun mushroom), are also widely studied for their biological effects (LESSNA et al, 2015;LIMA et al, 2010;LIMA et al, 2013;MARTINS et al, 2008). Martins et al (2008) reported that the polysaccharide-rich fraction of A. brasiliensis increased the microbicidal activity of macrophages against Candida albicans, stimulating hydrogen peroxide production and mannose receptor expression by peritoneal macrophages, which is important for non-opsonized microorganism attachment and phagocytosis.…”
Section: The Biological Effect Of Natural Products Obtained From Micr...mentioning
confidence: 99%